2017
DOI: 10.3390/s17071552
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid FPGA-Based System for EEG- and EMG-Based Online Movement Prediction

Abstract: A current trend in the development of assistive devices for rehabilitation, for example exoskeletons or active orthoses, is to utilize physiological data to enhance their functionality and usability, for example by predicting the patient’s upcoming movements using electroencephalography (EEG) or electromyography (EMG). However, these modalities have different temporal properties and classification accuracies, which results in specific advantages and disadvantages. To use physiological data analysis in rehabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 163 publications
0
22
0
Order By: Relevance
“…This will enable additional mobility features on the system such as active balancing and walking. Furthermore, although the system offers the possibility to enhance the control using biosignal-based control as discussed in [36,50,56,57], these aspects have not been evaluated in depth. Accordingly, in future we will evaluate the effect of biosignals on the control of the system and the effectiveness in stroke therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This will enable additional mobility features on the system such as active balancing and walking. Furthermore, although the system offers the possibility to enhance the control using biosignal-based control as discussed in [36,50,56,57], these aspects have not been evaluated in depth. Accordingly, in future we will evaluate the effect of biosignals on the control of the system and the effectiveness in stroke therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A ZC7030 consists of two parts: a Processing System (PS) (which is an ARM ® Cortex-A9 dual core CPU running at 1 GHz) and a Programmable Logic (PL) section, which is equivalent to an FPGA. 512 MB DDR3 SD-RAM are connected to the PS [50]. For communication, each ZynqBrain provides 5 duplex high-speed low-voltage differential signaling (LVDS) connections to connect the ACUs (for details see [40]).…”
Section: Decentralized Actuator-level Controllersmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we showed that during complex visual-motor activity it is possible to detect ERP activity related with target recognition and task-change processes. This can be used to improve the movement prediction when patients are instructed to execute specific movements by a therapist or serious game (Wöhrle et al, 2017 ). Our results support that for strong activities such as P300 and related processes single-trial ERP detection is in principle making use of features that are physiologically interpretable and expected.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the task of a patient in a therapeutic intervention is to try to move the affected arm. This task can be commanded by an event in a serious game for rehabilitation or given by the therapist (Wöhrle et al, 2017 ). Based on the strength of P300 expression, the strain on the patient could be estimated and the game automatically be adapted.…”
Section: Introductionmentioning
confidence: 99%